Cranial nerve involvement among COVID-19 survivors - Heidari, Mohammad Eghbal; Nazemi, Pershang; Feizabad, Elham; Beiranvand, Farzaneh; Afzali, Mahdieh (Frontiers in Neurology, 2023)
Introduction COVID-19 was first reported in November 2019 in China and rapidly spread across the globe. COVID-19 causes neurologic symptoms and complications, which may persist even after recovery in patients. The objective of this research was to determine the involvement of cranial nerves in COVID-19 survivors. Method This was a retrospective study. The study was conducted between March and July of 2022. The analysis included 98 patients with a certain positive polymerase chain reaction. SPSS software version 19 was utilized for data analysis. Results The average age of the participants was 40.47 years (8.81). The olfactory nerve was found to be the most frequently involved cranial nerve (36.7%). Over 20% of participants had a taste disorder. The findings from the regression analysis indicated that lung involvement and age have a direct and significant relationship with cranial nerve involvement and can serve as its predictors (p = 0.001). Conclusion It seems that cranial nerve involvement was sustained in COVID-19 patients who survived. In addition, elderly patients and patients with severe illnesses were more likely to show cranial symptoms. It is necessary to monitor COVID-19 survivors for neurological symptoms.